Palabra viviente (Banco Central del Ecuador, 1989)
Contiene: poesía de Jorge Arízaga, Mónica Astudillo M. Fernando Crespo páginas:, Monserrath Coello páginas:, Edison Estévez C., Germán Jácome V., Graciela Martínez de Rodríguez, Fernando Moreno O., Pedroico, Sandra Pérez, Virginia Roldán, Angelita Sánchez